Pengaruh Kepercayaan dan Kepuasan terhadap Loyalitas Pelanggan (Studi Kasus pada Nasabah Bank BRI Unit Sodong Kabupaten Tasikmalaya) - Rmdani, Gilang Tri (BISMA : Business and Management Journal, 2024)
This study aims to determine the effect of trust and satisfaction simultaneously and partially on customer loyalty at Bank BRI unit Sodong Kab. Tasikmalaya. The research method used in research is a quantitative approach with survey methods. The population in this study amounted to 100 respondents. The types of data used are classical assumption tests and multiple regression analysis using SPSS version 25. The results of this study show that trust and satisfaction simultaneously have a significant effect on customer loyalty. Partially, the trust has a significant effect on customer loyalty, as well as the partial satisfaction has a significant effect on customer loyalty